Serum and hair levels of zinc, selenium, iron, and copper in children with iron-deficiency anemia - Gurgoze, Metin Kaya; Olcucu, Ali; Aygun, A. Denizmen; Taskin, Erdal; Kilic, Mehmet (Humana Press Inc, 2006)
In the present study, the serum and hair levels of zinc, selenium, and copper were determined in children with iron-deficiency anemia (IDA). A total of 52 anemic children aged 1-4 yr constituted the study group. Forty-six healthy children acted as controls. The copper and zinc levels were measured with an atomic absorption spectrophometer. Serum and hair selenium was determined by a spectroflourometric method. The serum zinc and selenium concentrations in the IDA group were found to be significantly lower and serum copper significantly higher than those in the controls (p < 0.05). Lower iron, zinc, and selenium concentrations (p < 0.001) but not copper were found in hair (p > 0.05).
Keywords: iron deficiency anemia; zinc; selenium; copper; hair